2011
DOI: 10.1152/physiolgenomics.00049.2011
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor polyglutamine repeat length affects receptor activity and C2C12 cell development

Abstract: Testosterone (T) has an anabolic effect on skeletal muscle and is believed to exert its local effects via the androgen receptor (AR). The AR harbors a polymorphic stretch of glutamine repeats demonstrated to inversely affect receptor transcriptional activity in prostate and kidney cells. The effects of AR glutamine repeat length on skeletal muscle are unknown. In this study we examined the effect of AR CAG repeat length on AR function in C2C12 cells. AR expression vectors harboring 14, 24, and 33 CAG repeats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
0
17
0
2
Order By: Relevance
“…Cover slips were mounted on Prolong-Gold with DAPI (Molecular Probes) and micrographs were acquired using a fluorescence microscope (Axioimager, Zeiss). To quantify the densities of differentiated myotubes, the number of myonuclei was estimated by determining the average myonuclei number within a given field (56). MHC-positive-stained areas having a minimum number of three nuclei were considered to be differentiated myotubes.…”
Section: Methodsmentioning
confidence: 99%
“…Cover slips were mounted on Prolong-Gold with DAPI (Molecular Probes) and micrographs were acquired using a fluorescence microscope (Axioimager, Zeiss). To quantify the densities of differentiated myotubes, the number of myonuclei was estimated by determining the average myonuclei number within a given field (56). MHC-positive-stained areas having a minimum number of three nuclei were considered to be differentiated myotubes.…”
Section: Methodsmentioning
confidence: 99%
“…Recent data indicate that the CAG-repeat sequence in the AR gene modulates receptor transcriptional activity and affects muscle cell development in culture. 110 Additional work is required to clarify these findings.…”
Section: Androgen Receptor ( Ar )mentioning
confidence: 99%
“…Indeed, there is evidence that increased transcriptional activity of AR with shorter polyQ tracts corresponds to an increased risk of prostate cancer [138]. The effect of polyQ tract length on AR transcriptional activity may be cell-type dependent, however, as one study found a positive correlation between polyQ length and AR transcriptional activity in C2C12 skeletal muscle cells [139]. There are several potential mechanisms by which polyQ tract length and AR transcriptional activity may be related.…”
Section: Altered Trafficking and Functionmentioning
confidence: 99%